Applications of data mining in predicting the stability of Vitiligo - Singh, Gagandeep; Rathi, Kavita (International Journal of Computer Sciences and Engineering, 2019)
Vitiligo is growing at a good speed among the population and people have to go repeated surgeries to get rid of this disease. Though it’s not easy to define the stability, but it`s indispensable in the treatment of vitiligo. There have been many cases where people had gone for skin replacement surgery, but after sometime, white patches redeveloped on the skin. So the treatment goes on forever and patients get disheartened. The aim is to help people to identify the saturation of the disease before seeking the remedy which is skin transplantation. In this paper, improved J48 algorithm is used to predict the stability of vitiligo which gives optimal results. This algorithm uses the medical history of patients, Koebner phenomenon and VIDA score of sample data to feed into the systems and draw patterns to predict stability in the patients. We use various algorithms of data mining to extract useful information from data and check the accuracy of their medical history. The data includes the vitiligo patients, healthy people, the ones who have undergone surgery and the patients who haven’t undergone skin replacement and are still experiencing growth in their patches. With the prediction of various parameters, an optimal target value is predicted. In the end, we conclude with the most optimal algorithm which can be used to determine the stability of this disease and help the doctors and patients to determine the precise time of surgery.